(untitled) (Research, Society and Development, 2022)
Squamous cell carcinoma is the malignant neoplasm that most affects the oral cavity and, when not diagnosed early, often results in a compromised prognosis. Likewise, mucoepidermoid carcinoma, the most common type of malignant salivary gland tumor of unknown etiology, is also diagnosed based on subjective anatomopathological observations, without the implementation of mathematical image analysis methods. The objective of this work is to determine the histopathological fractal dimensions of the aforementioned cancers. Slides of oral squamous cell carcinoma, mucoepidermoid carcinoma and healthy tissue were used. Fractal dimensions were acquired using the box counting method. Analysis of fractal dimensions of squamous cell carcinoma nuclei (low and intermediate grade) revealed no significant difference between groups. Regarding the mean fractal dimensions of the cores of the mucoepidermoid carcinoma samples (control, moderate and well differentiated), the analysis showed that there was a significant difference between the control groups and the moderately differentiated 40x squamous cell carcinoma, with p<0.05. A significant difference was also identified between the control and 40x well-differentiated mucoepidermoid carcinoma, with p<0.001. No statistical significance was observed between the 40x well-differentiated 40x moderately differentiated mucoepidermoid carcinoma groups. Therefore, we can suggest that nuclear fractal dimension analysis is a useful tool for quickly diagnosing these conditions.